Analytical Study of Operational Efficiency of Industrial Boiler Plants Considering Building Thermophysics and Prospects for Integrating Heat Pumps - Yurii Burda; Ihor Redko; Yurii Pivnenko; Artem Cherednik; Roman Tkachenko (Energy Engineering and Control Systems)
This study presents an in-depth analytical investigation into the operational efficiency of boiler plants in industrial enterprises, incorporating the principles of building thermophysics as a fundamental component influencing energy performance. The research focuses on the interaction between the thermophysical properties of building enclosures, architectural design parameters, and the thermal regimes of boiler equipment. It highlights how building structures significantly impact heat losses and overall energy demand within the industrial environment, emphasizing the importance of considering these aspects in the operational analysis of heating systems. The study further explores the potential of modernizing existing boiler plants through the integration of heat pump technologies. Given the increasing demand for energy-efficient and environmentally sustainable solutions, heat pumps are examined as viable alternatives or supplementary components to conventional boiler systems.